2017
DOI: 10.1149/2.1531713jes
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and Passivation of a Silicon-Rich Austenitic Stainless Steel during Active-Passive Cycles in Sulfuric and Nitric Acid

Abstract: The high Si containing X1CrNiSi18-15-4 stainless steel (SS) spontaneously forms a protective oxide film that is mostly composed of mixed chromium and silicon oxides. This film ensures a good durability of the industrial facilities the alloy was designed for, containing very acidic electrolytes such as hot and concentrated nitric acid, HNO 3 , in presence of oxidizing species. In the present work, the chemistry of the oxide formed and the passivation kinetics of the alloy in sulfuric acid, H 2 SO 4 , and for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 49 publications
(89 reference statements)
4
10
0
Order By: Relevance
“…This is in accordance with the results of Tcharkhtchi et al who showed an increase of the oxide thickness of a 304L SS in nitric acid with the increase of the corrosion potential Ecorr [26]. for these SSs corroded in nitric acid media [26,43,61], the oxide is mainly composed of chromium with a small proportion of iron. Nickel oxide is not observed.…”
Section: Potential Vs She [V]supporting
confidence: 92%
“…This is in accordance with the results of Tcharkhtchi et al who showed an increase of the oxide thickness of a 304L SS in nitric acid with the increase of the corrosion potential Ecorr [26]. for these SSs corroded in nitric acid media [26,43,61], the oxide is mainly composed of chromium with a small proportion of iron. Nickel oxide is not observed.…”
Section: Potential Vs She [V]supporting
confidence: 92%
“…Nitric acid is a strong oxidant, and stainless steels spontaneously passivate in concentrated nitric acid solutions and remain passive at open-circuit potential (OCP) conditions. 24 Laurent et al investigated two stainless steels with low and high Si content in nitric acid and concluded that their passive layer was similar at the end of passivation. The naturally formed passive film over the ferrite is different than that of the austenite, giving rise to a typical Volta potential difference of 40-70 mV of numerous DSS's.…”
Section: Effect Of Nitric Acid Oxidation On the Passive Filmmentioning
confidence: 99%
“…The naturally formed passive film over the ferrite is different than that of the austenite, giving rise to a typical Volta potential difference of 40-70 mV of numerous DSS's. 12,13,19,25 Laurent et al 24 reported a chromium-rich oxide, in the form of chromia, that became further enriched in the passive film upon passivation in nitric acid, with the thickness, however, not been majorly altered. This may explain the reason why the Volta potential of ferrite and austenite of the DSS were similar after immersion in nitric acid.…”
Section: Effect Of Nitric Acid Oxidation On the Passive Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 32 ] The role of Si alloying on the evolution of the passive film was investigated using a similar activation‐passivation cycle, whereby a noticeable release of Si during activation confirmed the contribution of Si to the passive film of austenitic stainless steel. [ 33 ] However, the decay in the dissolution rate during passivation was found to predominantly follow the enrichment of Cr(III) oxides in the film. It indicates that in spite of enrichment in the passive film, the Si(IV) oxide did not contribute much to the passivity of stainless steel.…”
Section: Corrosion Case Studiesmentioning
confidence: 99%